Building a Transregional Governance Architecture for Electricity Integration in the Baja California–California Border Region: The Cases of Tijuana and Mexicali. (25th November 2018) - Muñoz‐Meléndez, Gabriela; López‐Vallejo Olvera, Marcela
Abstract : The integration of transboundary electricity markets is generally measured in terms of trade relations. We argue that to consolidate market integration it is necessary to build a transregional governance architecture where electricity exchanges are facilitated in competitive border cities with functional connecting infrastructure. This article focuses on the Mexican side of the Baja California–California border region, with Tijuana and Mexicali as cornerstone border cities. In building a governance architecture for Mexico, transboundary regulations and institutions are fundamental to support integration, as is the implementation of a comprehensive sustainability approach to drive competitiveness and address socioenvironmental externalities. An analysis of key regulations, infrastructure, economic and environmental sustainability, and social indicators was carried out to identify transregional governance architecture feasibility in the region. Results show that some aspects of such an architecture are already operating, but they seem to advance in different directions and at different paces on each side of the border. Meanwhile, binational coordination is still lacking at the various levels of government and layers of governance.